Synthesis, Physical Characterization, Antibacterial and Antifungal Activities of 2-((E)-1-(2-((E)-1-(2-Hydroxyphenyl)ethylideneamino) phenylamino) ethyl) phenol - A. A. Jarrahpour; A. F. Jalbout; J. M. Brunel; C. Loncle; S. Rezaei; B. Trzaskowski Trzaskowski (Molbank, 2006)
n/a